Comparing the Efficiency of Different Methods for Reliable Results in Ancient DNA NGS Workflow - Bence Kovács; Alexandra Gînguță; Petra Kiss; Kitti Maár; Oszkár Schütz; Gergely I. B. Varga; Endre Neparáczki (DNA, 2025)
Background/Objectives: Ancient DNA (aDNA) research workflows heavily depend on efficient aDNA extraction and NGS library preparation. In this study, we compared some of the commonly used laboratory protocols and compared the source of the bone material for sufficient and reliable results. Methods: We executed a three-phase study. First, we analyzed about 2000 previously processed archaic bone samples and conducted a comparative analysis. The second phase involved a controlled experiment of five ancient individuals, with internal control, to further investigate the efficiency of some of the methods. In the third phase, we made a comparison between the efficiency of two enzymes used for library preparation. Results: Samples made from Pars petrosa resulted in the highest yield of endogenous DNA and longer fragment sizes compared to tooth or skeletal samples. DNA extraction made by MinElute columns preserved slightly longer fragments than the handmade silica suspension. NGS libraries indexed using AccuPrime Pfx produced slightly more consistent insert sizes compared to GoTaq G2. Samples prepared with GoTaq G2 contained slightly more unique molecules. The duplication rates showed no significant impact from enzyme choice. Conclusions: Pars petrosa remains the most reliable source of aDNA, with the extraction method using MinElute columns. While AccuPrime Pfx ensures precise NGS library preparation, a more economical choice of the GoTaq G2 enzyme is a viable alternative for degraded archaic samples.